How close do you like your coffee? - Examining proximity and its effects in relationship coffee models. (April 2022) - Edelmann, Hanna; Quiñones-Ruiz, Xiomara F.; Penker, Marianne
Abstract: Relationship coffee models are generally characterized by a shortened value chain and efforts to achieve social, economic, and environmental sustainability. In three case studies with farmers organized in cooperatives in Peru and buyers in Austria or Germany, we analyzed the proximity among the geographically distant value chain actors. This paper aims to provide a more nuanced perspective on relational (organizational, institutional, cognitive, and social) proximity in relationship coffee models. The comparative analysis of the proximities in our case studies revealed that initial face-to-face contacts are required to build further proximity dimensions. Proximate relationship coffee models have led to more recognition, pride, a good reputation of the actors, higher coffee quality and thus farm-gate prices, and stable long-term relationships. However, relationship coffees require more coordination and communication among chain actors and advanced farmer skills and efforts to produce high-quality coffee. In relationship coffee models, farmers still depend on buyers and roasters to benefit from higher quality of their green coffee. Highlights: Relationship coffee models show geographical and relational proximity. They needed temporary geographical proximity first to build social or cognitive proximity. Relational proximity has led to higher quality and prices and stable, long-term relationships. Relational proximities cannot fully compensate for power imbalances. Farmers still depend on buyers to access the specialty coffee market and make profits.